MLST typing of Treponema pallidum subsp. pallidum in the Czech Republic during 2004-2017: Clinical isolates belonged to 25 allelic profiles and harbored 8 novel allelic variants - Vrbová, Eliška; Grillová, Linda; Mikalová, Lenka; Pospíšilová, Petra; Strnadel, Radim; Dastychová, Eliška; Kojanová, Martina; Kreidlová, Miluše; Vaňousová, Daniela; Rob, Filip; Procházka, Přemysl; Krchňáková, Alena; et al. (PloS one, 2019)
A recently introduced Multilocus Sequence Typing scheme for Treponema pallidum subsp. pallidum was applied to clinical samples collected from 2004 to 2017 from the two largest cities (Prague and Brno) in the Czech Republic. Altogether, a total of 675 samples were tested in this study and 281 of them were found PCR-positive for treponemal DNA and typeable. Most of the typed samples (n = 281) were swabs from primary or secondary syphilis lesions (n = 231), and only a minority were whole blood or tissue samples (n = 50). Swab samples from patients with rapid plasma regain (RPR) values of 1-1024 were more frequently PCR-positive (84.6%) compared to samples from patients with non-reactive RPR test (46.5%; p-value = 0.0001). Out of 281 typeable samples, 136 were fully-typed at all TP0136, TP0548, and TP0705 loci. Among the fully and partially typed samples, 25 different allelic profiles were identified. Altogether, eight novel allelic variants were found among fully (n = 5) and partially (n = 3) typed samples. The distribution of TPA allelic profiles identified in the Czech Republic from 2004 to 2017 revealed a dynamic character with allelic profiles disappearing and emerging over time. While the number of samples with the A2058G mutation was seen to increase (86.7% in 2016/2017), the number of samples harboring the A2059G mutation was found to have decreased over time (3.3% in 2016/2017). In addition, we found several allelic profile associations with macrolide resistance or susceptibility, the gender of patients, as well as patient residence.
Keywords: Young Adult; Multilocus Sequence Typing; RNA, Ribosomal, 23S; Male; Genotype; mladý dospělý; Česká republika; Drug Resistance, Bacterial; antibakteriální látky; Adult; dospělí; mužské pohlaví; syfilis; RNA ribozomální 23S; Czech Republic; DNA, Bacterial; DNA bakterií; Treponema pallidum; lidé; ženské pohlaví; Anti-Bacterial Agents; Humans; bakteriální léková rezistence; multilokusová sekvenční typizace; Syphilis; genotyp; Alleles; Female; alely